Influência de agentes clareadores na cor de resinas compostas de diferentes opacidades armazenadas em meios distintos - Lago, Maristela (2012)
The aim of this study was to evaluate the influence of two bleaching agents on color of one composite resin (Filtek Z350 XT - 3M ESPE) in the opacities of enamel and dentin, previously subjected to the action of deionized water or red wine. Sixty specimens (sp) were made for each composite resin using a metal matrix with 8 mm diameter and 2 mm thickness. Immediately after polymerization with LED (Emitter Schuster / Santa Maria Rio Grande do Sul, Brasil) for 40 s, the sp were polished with Diamond Pro discs (FGM / Joinvile SC, Brasil), and felt discs with diamond paste (Diamond Excel FGM / Joinvile SC, Brasil), then sp were washed in water and dried. The sp were divided into two groups for each opacity: immersed in red wine or deionized water for 14 days and then divided into three subgroups: one group subjected to bleaching with hydrogen peroxide 35% (Mix One Lot: 043 - Dental Villevie Brasil Ltda), one group submitted to bleaching with carbamide peroxide 16% (Mix Night - Lot: 007 - Dental Villevie Brasil Ltda) and one group not subjected to bleaching. Successive measurements were conducted 24 hours after polishing procedures, after 14 days of immersion on their respective immersion media, and after the action of the bleaching agents, using a spectrophotometer (SP60 EX-Rite / Grand Rapid Michigan, USA), with CIE L* a* b* system. Data were analyzed with t-test, one-way ANOVA, and Tukey (5%). Red wine caused significant color change in the composites in relation to water, and the enamel resin presented greater color change than the dentin resin. Bleaching agents partially removed the pigmentation of the sp which were immersed in wine, and the carbamide peroxide showed more significant results. The bleaching agents did not determine significant results when the sp were immersed in water. Red wine had great influence on the color change of composite resins and water caused no significant color change. The bleaching agents were capable of partial removal of the pigmentation produced by red wine.